PERSEPSI SISWA TERHADAP MATERI AJAR FIKIH INTEGRATIF DALAM PEMBELAJARAN PAI DI SMA - Muhammad Basri; Fadriati Fadriati (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Fiqh instruction at the senior high school level still tends to be normative and legalistic, creating a gap between the ideal transformative goals of fiqh education and its largely mechanistic classroom practices. This study aims to describe students’ perceptions of integrative fiqh teaching materials that connect cognitive, social, and spiritual dimensions within Islamic Education (PAI) at SMAN 1 Panyabungan Selatan. The study employs a quantitative approach using a descriptive survey method. The sample consists of all 20 ninth-grade students, selected through a saturated sampling technique. The instrument used is a closed-ended questionnaire based on a 1–4 Likert scale, comprising 20 items developed from three dimensions of perception: cognitive-integrative, social-contextual, and spiritual-applicative. Data analysis is conducted using descriptive quantitative techniques by calculating mean scores and categorizing them accordingly. The findings indicate that students’ perceptions of the integrative fiqh teaching materials are overall in the “very positive” category, with a mean score of 3.31. The cognitive-integrative dimension obtained the highest score (M = 3.40), followed by the spiritual-applicative dimension (M = 3.38), both categorized as very positive, while the social-contextual dimension received the lowest score (M=3.15), categorized as positive. In conclusion, the study affirms that students demonstrate a favorable reception toward the integrative approach. However, further strengthening is needed in the social-contextual dimension to ensure that fiqh materials are more relevant to the contemporary issues students encounter in their social lives. ABSTRAK Pembelajaran fikih di SMA masih cenderung bersifat normatif dan legalistik sehingga menimbulkan kesenjangan antara tujuan ideal pembelajaran fikih yang transformatif dengan praktik pembelajaran yang mekanistik. Penelitian ini bertujuan untuk mendeskripsikan persepsi siswa terhadap materi ajar fikih integratif yang mengaitkan dimensi kognitif, sosial, dan spiritual dalam pembelajaran PAI di SMAN 1 Panyabungan Selatan. Penelitian menggunakan pendekatan kuantitatif dengan metode survei deskriptif. Sampel penelitian adalah seluruh siswa kelas X yang berjumlah 20 orang, ditetapkan dengan teknik sampel jenuh. Instrumen yang digunakan berupa angket tertutup skala Likert 1-4 sebanyak 20 item yang dikembangkan berdasarkan tiga dimensi persepsi: kognitif-integratif, sosial-kontekstual, dan spiritual-aplikatif. Analisis data dilakukan secara deskriptif kuantitatif dengan menghitung rata-rata skor dan mengkategorisasikannya. Hasil penelitian menunjukkan bahwa persepsi siswa terhadap materi ajar fikih integratif secara keseluruhan berada pada kategori sangat positif dengan rata-rata skor 3,31. Dimensi kognitif-integratif memperoleh skor tertinggi (M=3,40), diikuti dimensi spiritual-aplikatif (M=3,38) pada kategori sangat positif, sedangkan dimensi sosial-kontekstual memperoleh skor terendah (M=3,15) pada kategori positif. Simpulan penelitian ini menegaskan bahwa siswa memiliki penerimaan yang baik terhadap pendekatan integratif, namun diperlukan penguatan pada aspek sosial-kontekstual agar materi fikih lebih relevan dengan persoalan aktual yang dihadapi siswa dalam kehidupan bermasyarakat.